Deficiência mental: prática educativa e reflexões de uma professora alfabetizadora - Silva, Larissa Maciel Gonçalves (2009)
Considering the school inclusion of students with mental disabilities in regular education, this study aims to discuss and understand the educational practice of the teacher who works in the literacy of mentally deficient students, the educational practice understood as essential for the proper school inclusion of these students. To achieve the proposed objective as a guideline for analysis, the Vygotsky studies about development and learning were chosen. As methodology of this research this study is based on a qualitative approach and involved the participation of the literacy teacher who had in classroom a student with mental disabilities. To construction the data, classroom observations were used with registers in field notes, and reflective interviews. The field notes were available to the conductor teacher for reading and reflections. The analysis of data indicates the crucial importance of educational practice in the process of inclusion of students with mental disabilities, demonstrating in their way that a change in the conception of the teacher promotes a change in attitude that reflects a more inclusive educational practice. The present study enabled a change in the way the teacher understands aspects of the classroom and the deficient student, as well as made possible a look at the possibilities and potentiality rather than the limitations from the disability. It is considered that these changes, so necessary for the effective inclusion of students with disabilities in the classroom, extrapolates the issue of specificity of students with mental disabilities and must be considered in the whole school context. Thus, the construction of this study shows that an inclusive educational practice is possible. This work contributes to the perception that the teacher can offer his or her students a practical education that characterizes itself by being inclusive, thereby contributing with teaching and school inclusion.